Using Affine Transformation to Obtain Approximate Offset Surface. (2009) - Zhao Zhao, Hongxing Hongxing; Ye Ye, Zhenglin Zhenglin; Meng Meng, Yaqin Yaqin; Wang Wang, Man Man
Abstract : For an arbitrary function C1 surface, we can use segment affine transformation to obtain a surface as its approximate offset surface. Each segment of the approximate offset surface and the corresponding segment of the original surface are proved to be of the same function type. After affine transformation, the geometric invariance of the original surface is proved to be retained in the approximate offset surface. The numerical example demonstrated the efficiency of our method.